EXPLORING STUDENT CREATIVITY AND COLLABORATION THROUGH PROJECT-BASED LEARNING WITH GOOGLE SITES - Akhmad Asyari; Lalu Ahmad Didik Meiliyadi; Ramdhani Sucilestari; Kurniawan Arizona (Jurnal Pendidikan Islam)
Project-based learning is essential for fostering creativity and collaboration among students, particularly in an increasingly digital educational landscape. This study investigates the effectiveness of implementing project-based learning using Google Sites in the educational context of the Physics Tadris Study Program at UIN Mataram. Employing a quasi-experimental design with a pre-test-post-test control group, the research involved a sample of 44 students selected through cluster random sampling from a population of 110 across eight classes. Data on student creativity and collaboration were collected through validated tests, questionnaires, and observation sheets, with results analyzed using t-tests and normalized gain values (N-gain). The findings revealed a significant enhancement in both creativity and collaboration among students, demonstrating that project-based learning via Google Sites not only improves essential skills but also creates a more interactive and enjoyable learning experience. The implications of this study suggest that integrating technology into project-based learning can effectively advance the goals of Islamic education, preparing students for collaborative and creative engagement in their future professional endeavors.